Improving learning quality through the implementation of electronic teaching materials - Firdaus, Hendi; Syafrizal, Syafrizal; Nulhakim, Lukman (Intelektual Pustaka Media Utama, 2024)
Education in automotive vocational high schools faces challenges in improving the quality of learning. This article discusses efforts to improve the quality of learning in automotive vocational schools through the implementation of electronic teaching materials. The implementation of technology in learning is an important solution in today's digital era. This article describes the advantages of using electronic teaching materials, such as flexibility, accessibility, and ease of content updates. This research involves collaboration between teachers, students, and technology experts to create relevant and interesting teaching materials. In addition, electronic teaching materials allow for more personalized learning adaptations, assist students with special needs, and facilitate distance learning. The results show that the implementation of electronic teaching materials in automotive vocational schools has a positive impact on learning, increasing students' motivation, expanding their knowledge, preparing students to enter the industrial world, and improving practical skills in the automotive field. Teachers also reported increased efficiency in the teaching process. The level of practicality of using electronic teaching materials reached 86.5%, with responses indicating that electronic teaching materials are very helpful in the learning.